Clout implementation of nursing care to give relief for children with pneumonia: a literature review - Nurhasanah Nurhasanah; Permaida Permaida (Media Keperawatan Indonesia, 2025)
Pneumonia is one of the most common acute infectious diseases that attacks children, and the highest cause of death is due to respiratory failure. Nurse sensitivity is necessary for implementing pneumonia nursing care, but how can it be said that implementation is perfect. This research aims to find out whether there is an impact of implementing nursing care to provide relief to children suffering from pneumonia. This research used a literature review method from the Google Scholar database from 2019 to 2023. It was found that six articles were the inclusion criteria. The research results showed that 66.7% (n=4) of articles explained that incomplete implementation of nursing could not completely overcome the problem of pneumonia. In comparison, 33.3% (n=2) of articles proved that complete implementation could overcome the problem of pneumonia in children. The role of nurses is very important in implementing nursing care. Implementing observation, education, therapeutic and collaborative actions into a series that are interconnected, cannot be separated, and have proven to have a relief impact on the problem of pneumonia in children